Analisis Pengembangan Bahan Ajar Tematik dalam Keterampilan Membaca di UPT SD Negeri Batu Jaya - Magdalena, Ina; Zhalila, Zhillan; Afrilia, Nanda Nurul (Lembaga Yasin AlSys, 2021)
This study aims to analyze the pattern of reading development that occurs in students. This research was conducted using a qualitative descriptive method. After making observations, interviews were then conducted with resource persons who understood how the teaching and learning process was and how students' abilities were in terms of understanding a reading. The thematic method is one form of innovation in the field of education that familiarizes students to think critically and accustoms teachers to have a high focus and always improve their abilities. From the results of research conducted, there were various student responses when retelling what they had read in front of the class. Students who have difficulty controlling their emotions will definitely have difficulty in retelling what they have read and there will be many words that are difficult to miss, and students who are too confident in themselves also tend to have difficulty controlling their existing emotions. They will be more active in telling stories but the essence of the story is not conveyed properly and eventually makes the audience bored. Small things like this will become habits that greatly affect the growth and development of students in the future. Character must be formed from an early age so that students have good and polite communication skills.